Efficacy of chlorhexidine/herbal formulation for microbial reduction in aerosol generated following ultrasonic scaling - A double-blinded randomized controlled trial - Lekha Ashokkumar; Vamsi Lavu; Kennedy Kumar Palraj; Suresh Ranga Rao; Subbusamy Kanakasabapathy Balaji (Wolters Kluwer Medknow Publications, 2023)
Background: Ultrasonic scaling is a potential source of aerosol contamination in dental clinics. The two primary sources of microbial load in aerosols are from the oral cavity and dental unit water line. Literature evidence suggest that the use of preprocedural mouth rinse reduce the bacterial load in aerosol generated during ultrasonic scaling. Aim: The aim of the study is to assess the comparative efficacy of reduction in viable bacteria in the aerosol at patient's chest area, doctor's mask area and two feet beside the patient following use of chlorhexidine/herbal formulation diluted in the water source by a randomized controlled clinical trial. Materials and Methods: Forty-five subjects (with chronic gingivitis) were matched for age, gender, and gingival index score. The subjects were randomized and received ultrasonic scaling with distilled water (control)/chlorhexidine (tTest)/herbal formulation (test). Aerosol produced during scaling was collected at patient's chest area, doctor's mask area, two feet beside the patient on blood agar plates, which were incubated at 37°C for 48 h and total colony forming units (CFUs) were counted. Results: A significant reduction in the total CFUs' counts was observed at all the three sites sampled in test groups (chlorhexidine group and herbal formulation group) as compared to control (P < 0.01). Conclusion: The addition of antiseptic agents to the water source contributed to a significant reduction of the cultivable microbial counts in the aerosol and hence can be used to reduce the risk of cross-infection during ultrasonic scaling.